Biopsy-proven CKD etiology and outcomes: the Chronic Kidney Disease Japan Cohort (CKD-JAC) study. Issue 2 (22nd March 2022) - Hamano, Takayuki; Imaizumi, Takahiro; Hasegawa, Takeshi; Fujii, Naohiko; Komaba, Hirotaka; Ando, Masahiko; Nangaku, Masaomi; Nitta, Kosaku; Hirakata, Hideki; Isaka, Yoshitaka; Wada, Takashi; Maruyama, Shoichi; et al.
ABSTRACT: Background: The Kidney Disease: Improving Global Outcomes guidelines advocate the cause–glomerular filtration rate (GFR)–albuminuria (CGA) classification for predicting outcomes. However, there is a dearth of data supporting the use of the cause of chronic kidney disease. This study aimed to address how to incorporate a prior biopsy-proven diagnosis in outcome prediction. Methods: We examined the association of biopsy-proven kidney disease diagnoses with kidney failure with replacement therapy (KFRT) and all-cause death before KFRT in patients with various biopsy-proven diagnoses ( n = 778, analysis A) and patients with diabetes mellitus labeled with biopsy-proven diabetic nephropathy (DN), other biopsy-proven diseases and no biopsy ( n = 1117, analysis B). Results: In analysis A, adding biopsy-proven diagnoses to the GFR–albuminuria (GA) classification improved the prediction of 8-year incidence of KFRT and all-cause death significantly regarding integrated discrimination improvement and net reclassification index. Fine–Gray (FG) models with KFRT as a competing event showed significantly higher subdistribution hazard ratios (SHRs) for all-cause death in nephrosclerosis 4.12 [95% confidence interval (CI) 1.11–15.2)], focal segmental glomerulosclerosis [3.77 (95% CI 1.09–13.1)] and membranous nephropathy (MN) [2.91 (95% CI 1.02–8.30)] than in immunoglobulin A nephropathy (IgAN), while the Cox model failed to show significant associations. Crescentic glomerulonephritis had the highest risk of all-cause death [SHR 5.90 (95% CI 2.05–17.0)]. MN had a significantly lower risk of KFRT than IgAN [SHR 0.45 (95% CI 0.24–0.84)]. In analysis B, other biopsy-proven diseases had a lower risk of KFRT than biopsy-proven DN in the FG model, with death as a competing event [SHR 0.62 (95% CI 0.39–0.97)]. Conclusions: The CGA classification is of greater value in predicting outcomes than the GA classification. Graphical Abstract: